Photophysical properties of betaxanthins: miraxanthin V – insight into the excited-state deactivation mechanism from experiment and computations. Issue 11 (19th January 2017) - Niziński, Stanisław; Wendel, Monika; Rode, Michał F.; Prukała, Dorota; Sikorski, Marek; Wybraniec, Sławomir; Burdziński, Gotard
Abstract : Fast radiationless S1 → S0 transition in photo-excited betaxanthins is due to conical intersection seam between S1 and S0 surfaces. Abstract : Miraxanthin V is a betaxanthin dye occurring in Caryophyllales plants. This work describes its photophysical properties in aqueous and alcoholic solutions. After excitation at λ exc = 480 nm (2.6 eV), transient absorption spectrum of the excited S1 state was observed (S1 → S n absorption band at λ probe = 394 nm). The S1 state population decays with two time constants (4.2 ps and 24.2 ps in water) corresponding to the photoexcited miraxanthin V in its two major stereoisomeric forms. The S1 state decay is mainly radiationless, since the fluorescence quantum yield is low ( Φ F = 0.003 in water, the smallest value among all of the studied betaxanthins). Strong correlations were obtained between the solvent viscosity and the S1 state lifetime in linear alcohols, as well as in methanolic solutions at low temperatures. These correlations suggest that intramolecular rotation or conformational relaxation precedes the S1 state decay. Full recovery of the electronic ground state S0 was observed after excitations at λ exc = 480 nm and 298 nm (4.2 eV), without forming the triplet T1 state or any photoproducts. Experimental results are complemented by the ab initio S0 state calculations using MP2 and DFT methods, and also by the excited-state calculations at the ADC(2) and TD-DFT levels of theory. The ab initio ADC(2) results give insight into the mechanism of the excited-state deactivation through the conical intersection region. We conclude that most probably the excited-state deactivation process is initiated by the rotation about the CN double bond, present in the chain linking the electron-donor catechol to the electron-acceptor dihydropyridine group, and it is followed by collective geometry changes involving a large rotation about the CC double bond. This mechanism seems to be universal for different betaxanthin dyes present in plants, and plays a photoprotective role.